Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/biom5042573
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and the Intestine

Abstract: Alcohol abuse is a significant contributor to the global burden of disease and can lead to tissue damage and organ dysfunction in a subset of alcoholics. However, a subset of alcoholics without any of these predisposing factors can develop alcohol-mediated organ injury. The gastrointestinal tract (GI) could be an important source of inflammation in alcohol-mediated organ damage. The purpose of review was to evaluate mechanisms of alcohol-induced endotoxemia (including dysbiosis and gut leakiness), and highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 117 publications
1
57
0
3
Order By: Relevance
“…Endotoxemia is closely related to the pathogenesis of ALD and stimulates the production of proinflammatory cytokines [36]. This study suggests that alcohol feeding increases serum endotoxin level.…”
Section: Discussionmentioning
confidence: 77%
“…Endotoxemia is closely related to the pathogenesis of ALD and stimulates the production of proinflammatory cytokines [36]. This study suggests that alcohol feeding increases serum endotoxin level.…”
Section: Discussionmentioning
confidence: 77%
“…Since blood from the intestines drains into the venous portal system, it is the liver that first encounters elevated levels of lipopolysaccharide (LPS) and other gut‐derived pathogen associated molecular patterns (PAMPs) (Patel et al. ; Szabo ). A growing body of evidence suggests that the resulting liver inflammatory response, primarily driven via LPS‐Toll‐Like Receptor‐4 (TLR‐4) interactions on liver‐resident Kupffer cells, promotes ALD pathogenesis (Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption causes intestinal inflammation, which is associated with accelerated polyposis [10,11]. We have shown that intestinal inflammation from alcohol is exacerbated by the disruption of circadian rhythms from shifting light:dark (LD) cycles [12,13,14].…”
Section: Introductionmentioning
confidence: 99%